Sticks and Stones in the Croatian Parliament: The Analysis of Insulting Practices - Tomić, Diana (Array, 2012)
This paper will present the study of insults in the Croatian Parliament using rhetorical analytical tool within an interdisciplinary theoretical framework, which includes rhetorical and discourse analysis and partly cognitive linguistic approach, as presented in works of a similar subject. To the already known reasons for studying insults in parliamentary discourse, we can add that they could indicate the degree of development of a national parliamentary discourse and, implicitly, of democracy itself. In more than twenty years of its existence, we have witnessed the development of the national political dialogue in the Croatian Parliament. The aim of this paper is to study the forms and functions of insults in the Croatian Parliament and compare them with recorded instances observed with similar methodology in the British and the Swedish parliament. The corpus for analysis includes transcripts of five sessions of the 6th Parliamentary assembly, convening during the period from September 2010 until October 2011 and 5 randomly selected sessions from each of the previous Parliamentary assemblies. Through the selection of corpus we tried to get information about the development of parliamentary discourse and an insight into the current situation. Modeled after similar works, the analysis included not only discussions but Aktualno prijepodne (i.e. Question time) as well. The levels of analysis are: forms of (un)parliamentary polarization, mitigation strategies and identification of in-group identity and inter-group dissent by usage of insults and derogatory terms. Reactions to the insults were analyzed as part of the identification process of in-group identity and inter-group dissent, as it was noted that the MPs were often offended and wanted to comment on an insult that was not personally addressed to them. The results show that the political representatives of the Croatian Parliament are polarized, much like those in the British Parliament. The offensive expressions, based on logos, are pathos-oriented with frequent occurrences of ad hominem arguments. Unlike the British Parliament, rhetorical question, irony and sarcasm are not represented to a large extent. The most mitigation strategies include attribution transfer, followed by juxtaposition of opposing concepts - contempt as opposed to respect, while the formulation of insults as questions is not as represented. Direct expressions of insults without attempts to mitigate are also quite frequent in parliamentary debates and they serve to encourage conflict between ruling and opposition parties and of course, to entertain the audience. However, the amount of direct insults, which has slightly decreased in recent parliamentary assemblies, shows underdevelopment of the Croatian political discourse, with a deliberate lack of analogies and parallelisms. Linking of like-minded politicians is shown through forms of address, the procedures to respond to offensive phrases (e.g. three representatives replicated using the same insult in response to an insult), labeling and stereotypes. Insults in the 6th Parliamentary assembly often refer to corruption, and moral characteristics of MPs. Since corruption charges are current political issue, it is not surprising that this is the basis for insults. However, based on the analyzed sessions, it is difficult to set aside a typical Croatian conceptual basis, like intellectual abilities, which was traditionally an important aspect of British political discourse and their basis for forming an insult. The analysis shows that the insults are generally generated by political affiliation, and stereotypes associated with the disagreement about current political issues (war, war crimes, privatization, corruption, etc.) Finally, the rhetorical function of an insult in Croatian Parliament, as in the British Parliament, is pathos-oriented and fulfills all three functions of the aforementioned term: to strengthen the connection between the group and to re-establish the rhetorical balance, entertain the audience (MPs and the public in general), and act on the emotions of the audience by opening some difficult political issues, social categories such as fear, dissatisfaction, or the interests of certain groups.